Statin Utilization for Primary Prevention of Cardiovascular Disease in Patients Developing First ST‐Segment Elevation Myocardial Infarction: A Malaysian Retrospective Cohort Study - Abdullah Faiz Zaihan; Shairyzah Ahmad Hisham; Aina Yazrin Ali Nasiruddin; Chia Siang Kow; Syed Shahzad Hasan; Dinesh Sangarran Ramachandram (Health Science Reports)
ABSTRACT Background and Aims This retrospective cohort study aimed to determine the utilization rate of statin therapy for primary prevention of cardiovascular disease (CVD) and factors associated with its use in patients prior to experiencing their first ST‐elevation myocardial infarction (STEMI). Methods The study included 177 patients admitted for their first episode of STEMI at a Malaysian secondary hospital in 2020. Data were retrospectively collected from the electronic health information system. Logistic regression analysis was performed to identify significant predictors of statin therapy utilization for primary prevention. Results Of the 177 patients, only 15.8% (n = 28) had been prescribed statin therapy for the primary prevention of CVD prior to their first STEMI. Hypertension and dyslipidemia were identified as significant predictors of statin use, with adjusted odds ratios (AOR) of 9.570 (95% CI: 1.859–49.281) and 37.900 (95% CI: 6.716–213.87), respectively. Follow‐up data indicated significantly reduced cholesterol levels post‐STEMI, demonstrating the lipid‐lowering effectiveness of statin therapy. Conclusion This study highlights the low utilization rate of statin therapy for primary prevention of CVD among patients prior to their first STEMI. Despite the proven effectiveness of statins in lowering cholesterol levels post‐STEMI, there is a need to enhance awareness, adherence to guidelines, and efforts to achieve LDL‐C targets through appropriate statin therapy.